Understanding the healthcare experiences and needs of African immigrants in the United States: a scoping review - Ogbonnaya I. Omenka; Dennis P. Watson; Hugh C. Hendrie (BMC, 2020)
Abstract Background Africans immigrants in the United States are the least-studied immigrant group, despite the research and policy efforts to address health disparities within immigrant communities. Although their healthcare experiences and needs are unique, they are often included in the "black" category, along with other phenotypically-similar groups. This process makes utilizing research data to make critical healthcare decisions specifically targeting African immigrants, difficult. The purpose of this Scoping Review was to examine extant information about African immigrant health in the U.S., in order to develop lines of inquiry using the identified knowledge-gaps. Methods Literature published in the English language between 1980 and 2016 were reviewed in five stages: (1) identification of the question and (b) relevant studies, (c) screening, (d) data extraction and synthesis, and (e) results. Databases used included EBSCO, ProQuest, PubMed, and Google Scholar (hand-search). The articles were reviewed according to title and abstract, and studies deemed relevant were reviewed as full-text articles. Data was extracted from the selected articles using the inductive approach, which was based on the comprehensive reading and interpretive analysis of the organically emerging themes. Finally, the results from the selected articles were presented in a narrative format. Results Culture, religion, and spirituality were identified as intertwined key contributors to the healthcare experiences of African immigrants. In addition, lack of culturally-competent healthcare, distrust, and complexity, of the U.S. health system, and the exorbitant cost of care, were identified as major healthcare access barriers. Conclusion Knowledge about African immigrant health in the U.S. is scarce, with available literature mainly focusing on databases, which make it difficult to identify African immigrants. To our knowledge, this is the first Scoping Review pertaining to the healthcare experiences and needs of African immigrants in the U.S.